PENGARUH PENDIDIKAN DAN UPAH TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA KOTA DI PROVINSI SUMATERA BARAT - Arivetullatif, Arivetullatif; Afrianti, Rini; Murni, Yanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract.: The labor force participation rate is one of the indicators to assess economic progress. This study aims to understand the impact of education and wages, both individually and together, on the labor force participation rate in West Sumatra Province. The method applied in this study is a quantitative method. The focus of this study is cities in West Sumatra Province in the period 2018 to 2022. In this study, the number of samples taken was 35. Data analysis was carried out using multiple linear regression, using SPSS version 23. The findings of the study show the multiple linear regression equation Y = -452.203 + 5.306X1 -0.680X2, and based on partial analysis, the education variable shows a significant effect on the labor force participation rate in cities in West Sumatra Province. Meanwhile, the wage variable shows a negative and insignificant effect on the labor force participation rate in the area. Overall, both education and wages have a significant effect on the labor force participation rate in cities in West Sumatra Province. It is hoped that the government can continue to pay attention to areas that still face obstacles in education and improve worker welfare to encourage increased labor force participation. Keywords: Education, wages, labor force participation rate